Relationship of rheumatoid factor positivity to prevalence of joint manifestations in type 2 diabetes which are unrelated to rheumatoid arthritis - Raj, Sumesh; Vijayan, Rajesh; Rajan, G. V.; Sugathan, Reshma (International Journal of Research in Medical Sciences, 2017)
Background: The present study was designed to investigate the relationship of rheumatoid factor positivity to the prevalence of joint manifestations in type 2 diabetes which are not attributable to rheumatoid arthritis. Methods: We evaluated 192 type 2 diabetes patients with rheumatological complications and age and sex matched non-diabetic controls for rheumatoid factor (RF) positivity. Diabetic patients with frozen shoulder, LJM syndrome, carpal tunnel syndrome, trigger finger, DISH and Dupuytren’s contracture were evaluated for RF positivity. Results: RF was positive in 47 patients (24.4%) when compared to controls (4.2%). RF positivity was associated with an increased prevalence of joint manifestations in diabetic group when compared to controls. RF positivity was not related to the duration of diabetes nor was it related to long term glycemic control. Conclusion: RF positivity resulted in an increased prevalence of joint manifestations in diabetes, which were unrelated to rheumatoid arthritis.